2020
DOI: 10.25259/ijms_28_2020
|View full text |Cite
|
Sign up to set email alerts
|

Protecting health-care professionals and workers (other than COVID-19 management facilities) from contamination during COVID-19 pandemic (March 26, 2020 – India)

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-Share Alike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as the author is credited and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Such increased rates of reported problems even in general public in turn indicates how the frontliners are at even greater risk to experience mental health problems during this crucial time. [15,16] Outbreak of COVID-19 has led to a sudden shift in the workforce behavior around the globe posing immense burden on the health-care system. In our study, around 30% and 44% male doctors reported mild and moderate level of stress, respectively, whereas 70% and 56% female doctors reported mild and moderate level of stress, respectively, again indicating an increase in the stress levels being experienced by the health-care staff during this time.…”
Section: Discussionmentioning
confidence: 99%
“…Such increased rates of reported problems even in general public in turn indicates how the frontliners are at even greater risk to experience mental health problems during this crucial time. [15,16] Outbreak of COVID-19 has led to a sudden shift in the workforce behavior around the globe posing immense burden on the health-care system. In our study, around 30% and 44% male doctors reported mild and moderate level of stress, respectively, whereas 70% and 56% female doctors reported mild and moderate level of stress, respectively, again indicating an increase in the stress levels being experienced by the health-care staff during this time.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been several guidelines published for protecting Indian health care workers from contamination during COVID-19 pandemic. [34] The Ministry of AYUSH in India has also issued self-care guidelines and preventive health measures to boost immunity with special references to respiratory health, based off Ayurvedic research and literature. [35] Recently, the Indian government also recommended the use of hydroxychloroquine as a preventive measure to protect frontline workers from the SARS-CoV2 infection.…”
Section: Resultsmentioning
confidence: 99%
“…There have also been several guidelines published for protecting Indian health care workers from contamination during COVID-19 pandemic. [ 34 ]…”
Section: Discussionmentioning
confidence: 99%
“…Singapore and South Korea deployed HWs from other disciplines and recent medical graduates, as well as China moved HWs to Wuhan from other provinces. Similar practices could be adapted in Indian context 33 . Mobilizing existing CHWs and health volunteers is also important strategy utilized by China and could be key information source to dispel myths in the Indian community, but also perform symptom screening and contact tracing 34 .…”
Section: Interventions At 'Institutional Level'mentioning
confidence: 99%